2019
DOI: 10.3390/app9132613
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Technology Competition of Graphene Biomedical Technology Based on Patent Analysis

Abstract: Graphene, with high biocompatibility, physiological solubility and stability, has been reported as an emerging material for biomedical applications such as biosensors, drug delivery, and tissue engineering. Recently, identifying the technological competition (TC) of graphene biomedical technology has received worldwide attention from stakeholders. However, few studies have attached great importance to review the TC of this field by the analysis of patents. The main objective of this study is to develop a new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 102 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…The names of clusters were proposed, which made it possible to identify research sub-areas and main research issues, in which the authors of the publications used technology development roadmaps (Table 1). Analysis of patent development patterns (Jeong and Yoon, 2015;Yu and Zhang, 2019;Trappey et al, 2019;Zhou et al, 2019;Yang et al, 2019);…”
Section: Resultsmentioning
confidence: 99%
“…The names of clusters were proposed, which made it possible to identify research sub-areas and main research issues, in which the authors of the publications used technology development roadmaps (Table 1). Analysis of patent development patterns (Jeong and Yoon, 2015;Yu and Zhang, 2019;Trappey et al, 2019;Zhou et al, 2019;Yang et al, 2019);…”
Section: Resultsmentioning
confidence: 99%
“…Technology competition of graphene biomedical technology has been analyzed based on patent analysis. Patent analysis with text mining was used to forecast emerging technologies in wireless power transfer [34].…”
Section: Patent Analysismentioning
confidence: 99%
“…Patents are considered one of the most reliable data resources for technological opportunity identification [9][10][11], due to their integrity of technical information, standardization of document management, and availability of data. Studies have suggested methods of identifying technological opportunities through drawing patent citation networks, to identify core patents as technological opportunities [12][13][14], establishing a morphological matrix to identify prioritized combinations of patents as technological opportunities [15], and constructing semantic patent maps, to identify patents hotspots and outlier patents as technological opportunities [16][17][18].…”
Section: Introductionmentioning
confidence: 99%